Contributing factors to early recurrence of ventricular fibrillation during out-of-hospital cardiac arrest: An observational retrospective study. (September 2020) - Jost, Daniel; Hong Tuan Ha, Vivien; Trichereau, Julie; Frattini, Benoit; Derkenne, Clément; Lemoine, Sabine; Lemoine, Frédéric; Jouffroy, Romain; Kedzierewicz, Romain; Briche, Frédérique; Diegelmann, Pascal; Bihannic, René; et al.
Abstract: Introduction: In out-of-hospital cardiac arrest (OHCA), external electric shock (EES) is recommended for treating ventricular fibrillation (VF). Refibrillation commonly occurs within one minute post-shock. We aimed to investigate refibrillation times and identifyclinical and electrical factors associated with them. Materials and methods: This retrospective observational study, based on the Paris Fire Brigade database, included non-traumatic OHCA over 18 years of age who received at least one shock with an AED from Basic Life Support (BLS) rescuers and from which we randomly selected a sample to measure the refibrillation-times. Without prior reference to it in the literature, we classified the refibrillation-time into two modalities according to whether it was above or below the median-time. We performed multiple regression analysis to assess associations between refibrillation-time and potential explanatory factors. Results: Among 13, 181 patients who experienced OHCA from January 2010 to January 2014, we analysed AED data from 215 patients (590 shocks), 82.1% males, median age 61[IQR: 52−75] years. Most of them occurred at home (57%), were witnessed (87%), and were shockable (88.8%). A median of 5[4–7] EES/patients were delivered. The median-time from shock to refibrillation was 25[13−44] s. Multivariate analysis showed that a shorter post-shock hands-off time favoured earlier refibrillation (p = 0.034), as well as older age (p = 0.002) (Fig. 2, Supplementary table). Conclusion: In non-traumatic OHCA, most refibrillations occurred within 45-s post-shock. Age and post-shock hands-off time were the two contributing factors to time to refibrillation.